Effects of amoxicillin/clavulanic acid on the pharmacokinetics of valproic acid - Lee SY; Huh W; Jung JA; Yoo HM; Ko JW; Kim JR (Dove Medical Press, 2015)
Soo-Yun Lee,1 Wooseong Huh,2 Jin Ah Jung,3 Hye Min Yoo,2 Jae-Wook Ko,1,2 Jung-Ryul Kim2,4 1Department of Health Sciences and Technology, SAIHST, Sungkyunkwan University, 2Department of Clinical Pharmacology and Therapeutics, Samsung Medical Center, Seoul, 3Department of Clinical Pharmacology, Inje University, Busan Paik Hospital, Busan, 4Department of Clinical Research and Evaluation, SAIHST, Sungkyunkwan University, Seoul, Republic of Korea Abstract: Valproic acid (VPA) is mainly metabolized via glucuronide, which is hydrolyzed by β-glucuronidase and undergoes enterohepatic circulation. Amoxicillin/clavulanic acid (AMC) administration leads to decreased levels of β-glucuronidase-producing bacteria, suggesting that these antibiotics could interrupt enterohepatic circulation and thereby alter the pharmacokinetics of VPA. This study aimed to evaluate the effects of AMC on the pharmacokinetics of VPA. This was an open-label, two-treatment, one-sequence study in 16 healthy volunteers. Two treatments were evaluated; treatment VPA, in which a single dose of VPA 500 mg was administered, and treatment AMC + VPA, in which multiple doses of AMC 500/125 mg were administered three times daily for 7 days and then a single dose of VPA was administered. Blood samples were collected up to 48 hours. Pharmacokinetic parameters were calculated using noncompartmental methods. Fifteen subjects completed the study. Systemic exposures and peak concentrations of VPA were slightly lower with treatment AMC + VPA than with treatment VPA (AUClast, 851.0 h·mg/L vs 889.6 h·mg/L; Cmax, 52.1 mg/L vs 53.0 mg/L). There were no significant between-treatment effects on pharmacokinetics (95% confidence interval [CI]) of AUClast and Cmax (95.7 [85.9–106.5] and 98.3 [91.6–105.6], respectively). Multiple doses of AMC had no significant effects on the pharmacokinetics of VPA; thus, no dose adjustment is necessary. Keywords: drug–drug interaction, pharmacokinetics, enterohepatic circulation